Degradabilidad in situ de la Materia Seca y Proteína Cruda de las Hojas y Peciolo del Pisonay (Erythrina falcata) - Cárdenas-Villanueva, Ludwing A. (2016)
The study aimed to determine the chemical composition and ruminal degradability of dry matter (DM) and crude protein (CP) of Erythrina falcata at 105, 120 and 135 days of regrowth. Leaves and petiole samples were dried and 8 g of dry grounded samples were placed in nylon bags in the rumen of three male goats during 0, 24, 48 and 72 hours. The DM and CP values were 24.4 and 21.4% at 105, 24.8 and 23.2% at 120 and, 27.2 and 24.4% at 105 days respectively. The ruminal degradability of potentially degradable insoluble fraction of DM and CP was 29.6 and 42.9% at 105, 24.3 and 31.4% at 120 and, 14.9 and 24.1% at 135 days, respectively, and the effective degradability of DM and CP was 41.3 and 41.2% at 105, 36.5 and 30.3% at 120 and, 32.3 and 30.5% at 135 days respectively. The study showed a higher protein advantage in goats at 105 days of growth of E. falcata foliage.